Mechanical and Damping Properties of Wood Plastic Composite Modified by Ground Waste Rubber Tire. Issue 3 (August 2017) - Luo, Jianlin; Li, Qiuyi; Shang, Huaishuai; Gao, Song; Zhang, Chunwei; Sun, Shengwei
Recycled WPC product using in construction industry occasionally falls short of expectation owing to lack of sufficient ductility and damping capacity, ground waste rubber tire (WTR) with substantial elasticity can be a proper candidate to meet the gap when adding appropriately. Here, WTR after alkali activation was blended in waste wood flour (WWF) treated with compatibilizer, the mixture after oven-dried was subsequently filled into thermoplastic recycled polyethylene (RPE) or polypropylene (RPP) base (WTR/WPC) through hot-press molding process. Mechanical properties (tensile strength ft, flexural strength fb, impact strength fa ) of RPE-based and RPP-based WTR/WPC strips with 4 different WTR fractions were characterized. Its damping properties (loss factor β) were measured and identified by ultrasonic agitation and half-power bandwidth identification method, respectively. The coarse WTR has balanced but stable effect on the improvement of ft, fb, fa, and β of WTR/WPC with rigid RPP base than that with flexible RPE, which attributes to the synthetic effects of good deformation capacity of coarse WTR themselves, strong bridging capacity of WWF, and sufficient stick-slip intercalation between WWF or WTR and rigid RPP. The ft, fb and fa, β with 5% coarse WTR of RPP-based WTR/WPC reaches 12.32 MPa, 15.74 MPa; 2.58 MPa and 0.0853, respectively.